Catherine de Médicis (1519–1589) et le portrait : esquisse d’une collection royale au féminin - Turbide, Chantal (RACAR : Revue d'art canadienne / Canadian Art Review, 2005)
This paper represents the first scholarly analysis of the collection of portraits amassed by Catherine de' Medici (1519–1589), Queen of France, during her reign of more than forty years. The fact that no portrait has yet been identified as having belonged to her may explain why this subject has never been broached. This paper will demonstrate that Catherine had a vision in her collecting, thus contradicting Louis Dimer’s 1926 opinion that she collected portraits without any specific program in mind. This article begins with a review of the main sources. Following Catherine’s death, more than 250 portraits in the Hôtel de la Reine in Paris were listed in the inventory drawn up in the summer of 1589. Some documents, mainly correspondence, deal with their acquisition and name French and Italian artists. This article then looks at other European Renaissance collections of portraits. Comparisons with these reveal that Catherine de' Medici's collection – consisting of portraits of family members, political figures, rulers, kings and queens – was among the most important of her time. Moreover, it will be shown that Catherine seems to have introduced to France the new concept of an exhibition space, a gallery, entirely devoted to portraits, which was to become very popular in the seventeenth century. This essay closes with a case study exploring the exchanges of portraits between France and England in 1571 and, in particular, 1580 and 1582, thus exposing the symbolic function of portraiture in the political sphere and the role of the diplomatic corps.